A multilevel analysis of a randomized clinical trial comparing adjunctive moxifloxacin versus amoxicillin/metronidazole for the treatment of aggressive periodontitis - Carlos-Martín Ardila; Jader-Alexander (Wolters Kluwer Medknow Publications, 2021)
Background: It was documented that the clinical outcomes of mechanical periodontal treatment can fluctuate not merely concerning patients but equally among various tooth sites in the subject. This trial evaluates the clinical parameters related with the patient, tooth, and site that generate more changes in clinical attachment level (CAL) gain and probing depth (PD) reduction, using moxifloxacin (MOX) versus amoxicillin plus metronidazole (AMOX + ME) as adjuncts to scaling and root planing (SRP), in comparison to SRP only, post-therapy in generalized aggressive periodontitis (GAgP). Materials and Methods: The analysis of this clinical trial included 6012 tooth sites at 1002 teeth in 36 patients; they were randomly assigned to three protocols: Systemically intake of MOX or AMOX + ME plus SRP, or SRP + placebo for 7 days. The clinical effect of the patient, tooth, and site characteristics, in terms of CAL gain and PD reduction, was explored using a multilevel linear model. P < 0.05 was statistically significant. Results: Following 6 months of treatment, the differences between the groups were statistically significant, favoring the MOX and AMOX + ME protocols (P < 0.0001). Moreover, the multilevel model showed that adjunctive MOX, AMOX + ME, non-molar, and interproximal sites were the features that contribute significantly to CAL improvement, and PD decreases in GAgP (P ≤ 0.001 for all). Conclusion: The most relevant characteristics for the changes in CAL increase and PD diminution, after adjunctive antimicrobials, were ascribable to the features related to the tooth. MOX and AMOX + ME, non-multi-radicular-tooth, and interdental sites indicated superior clinical gains at the tooth and site levels in GAgP.